A Community-Informed Virtual World-Based Cardiac Rehabilitation Program as an Extension of Center-Based Cardiac Rehabilitation: MIXED-METHODS ANALYSIS OF A MULTICENTER PILOT STUDY. Issue 1 (25th January 2023) - Brewer, LaPrincess C.; Abraham, Helayna; Kaihoi, Brian; Leth, Shawn; Egginton, Jason; Slusser, Joshua; Scott, Christopher; Penheiter, Sumedha; Albertie, Monica; Squires, Ray; Thomas, Randal; Scales, Robert; et al.
Abstract : This study assessed the feasibility and acceptability of a novel virtual world-based CR (VWCR) program, Destination Rehab, as an extension of a conventional center-based CR program. The VWCR program is a feasible, highly acceptable, and innovative platform to potentially influence health behaviors and CV risk and may increase accessibility to disadvantaged populations with higher CV disease burdens. Abstract : Purpose: Innovative methods for delivering cardiac rehabilitation (CR) that provide strategies to circumvent the mounting barriers to traditional CR have the potential to widen access to a well-established secondary prevention strategy. Our study assesses the feasibility and acceptability of a novel virtual world-based CR (VWCR) program, Destination Rehab, as an extension of a conventional center-based CR program. Methods: Adult cardiac patients hospitalized at Mayo Clinic hospitals with a diagnosis for CR and ≥1 modifiable, lifestyle risk factor target—sedentary lifestyle (<3 hr physical activity/wk), unhealthy diet (<5 servings fruits and vegetables/d), or current smoking (>1 yr)—were recruited. Patients participated in an 8-wk health education program using a virtual world (VW) platform from a prior proof-of-concept study and a post-intervention focus group. Primary outcome measures included feasibility and acceptability. Secondary outcome measures included changes from baseline to post-intervention in cardiovascular (CV) health behaviors and biometrics, CV health knowledge, and psychosocial factors. Results: Of the 30 enrolled patients (age 59.1 ± 9.7 yr; 50% women), 93% attended ≥1 session and 71% attended ≥75% of sessions. The overall VWCR experience received an 8 rating (scale 0-10) and had high acceptability. Clinically relevant trends were noted in CV health behaviors and biometrics, although not statistically significant. Conclusions: The VWCR program is a feasible, highly acceptable, and innovative platform to potentially influence health behaviors and CV risk and may increase accessibility to disadvantaged populations with higher CV disease burdens.